A Comparison of Ideas in the Development and Governance of National Parks and Protected Areas in the US and Canada - Warner, Rosalind (International Journal of Canadian Studies / Revue internationale d’études canadiennes, 2008)
This paper uses a comparison of ideas in US and Canadian national parks history and governance to explain the rationale for the development of national parks and protected areas. Comparisons of the Canadian and US national parks history have either noted few significant differences, or have argued that there has been far less emphasis on preservation in Canadian parks governance. This paper uses two main axes to compare ideas about parks governance in the US and Canada: the first involves the discursive and cultural justification for restricting development; and the second is the degree of governmental leadership and conscious planning, or statism, that goes into parks governance. A survey of the respective histories of parks governance leads to the conclusion that differences between the US and Canada in parks governance exist. Nevertheless, these are largely a result of the historical interaction and relationship between the two countries, rather than inherent cultural differences or similarities in notions of "wilderness." Conclusions centre on the effects of the tendency for Canadian patterns of economic development to produce greater path dependency and hence to restrict resistance to economic development within parks.